Dilemmas of a military ruler : a political study of the Zia regime - Masoom, Abdul Latif (Dhaka : Afsar Brothers, 2000)
Account of the Bangladesh government during the rule of Ziaur Rahman, former president and founder of the Bangladesh Nationalist Party.
Includes bibliographical references (p. 265-283) and index.
Keywords: Rahman, Ziaur; Bangladesh Nationalist Party; Bangladesh -- Politics and government -- 1971-